Foreword [Occupational Safety and Hygiene III] - Arezes, P. (2015)
[Excerpt] This book is the third edition of this series of publications that are entitled “Occupational Safety and Hygiene”. The main contributions for this book were, once again, the works previously submitted and approved to be presented at the annual Symposium of the Portuguese Society of Occupational Safety and Hygiene (SPOSHO), which is celebrating its 11th edition in 2015. The SHO2015—International Symposium on Occupational Safety and Hygiene, similarly to the past seven years, was held in the School of Engineering at University of Minho in Guimarães, Portugal.